The Amateur Hour : A History of College Teaching in America - Zimmerman, Jonathan, 1961- (Book collections on Project MUSE., 2020)
"This is the first book-length history of college teaching in America, which traditionally has been a matter of imitation for instructors rather than formal training. Drawing on extensive unpublished manuscript material, the book weaves together student, faculty, and administrative perspectives in a rich portrait of undergraduate classrooms across time. It also documents long-standing but largely unknown efforts to reform college instruction by making it more personal, especially at research institutions"--